PENERAPAN CROSS-CULTURAL UX DALAM WEBSITE MOOI FILTERS - Zidan Jamili Muslim; Muhamad Fikri (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of Cross-Cultural User Experience (UX) on the MOOI Filters website and to develop a more adaptive design solution for international users. The research is motivated by the growing importance of cross-cultural user experience in supporting global market expansion, particularly for local Indonesian business websites. The main issues identified include unclear information structure, unsystematic navigation, and content delivery that does not fully meet the needs of international users. The research employs a Design Thinking method with a descriptive qualitative approach, consisting of the stages of empathize, define, ideate, prototype, and testing. Data were collected through direct website observation, UX element analysis based on Cross-Cultural UX theory, and expert validation using Heuristic Evaluation based on Nielsen’s ten usability principles. The redesign process focuses on simplifying navigation, improving information hierarchy, restructuring visual elements, and presenting more explicit and globally understandable content. The results indicate a significant improvement in design quality. The average UX evaluation score increased from 2.87 to 4.22 (on a 1–5 scale), reflecting an improvement from “moderate” to “good–very good.” The most notable improvements were observed in recognition rather than recall, help and documentation, and error recovery. These findings demonstrate that the Cross-Cultural UX approach effectively enhances information clarity, access efficiency, and global readiness. Therefore, it can be concluded that this approach is a relevant solution for reducing interaction barriers and improving overall user experience.